PENGARUH UKURAN KAP, FEE AUDIT, HUBUNGAN DENGAN KLIEN, KOMITMEN PROFESIONAL DAN PERSAINGAN ANTAR KAP, TERHADAP INDEPENDENSI KANTOR AKUNTAN PUBLIK (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru, Medan, Padang) - Sukamdani, M.; Sofyan, Azhari; ', Zirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research test the size of public accountant firm, audit fee, relations with client, profesional commitment and public accountant firm competition on the implementation of independence public accountant firm.The population of this research were the whole auditors who work in the public accountant firm in pekanbaru, medan, padang. And This research used 63 sample of questionnaires response from staff of public accountant firm in Pekanbaru, Medan, Padang.Analysis model used in this study is the multiple linear regression analysis with SPSS Version 20.00. The research proves the size public accountant firm, audit fee, relations with client, professional commitment have significant influence to independence of public accountant individually. But public accountant firm competition at a significant level (>0,05) is contrary. Simlutaneous regression test (F-test) showed that all dependent variable have significant influence to the dependent variable, the coefficient determination (R2) effect by all independent variable are 75,2% while the remaining 24,8% influence by other variables were not examined in this study.Keywords : independence, the size of public accountant firm, audit fee, client, commitment and competition